Biofuels : (Academic Press, 2011)
Global concern for energy security and environmental protection has put great emphasis on the search for alternative energy sources, particularly for the transport sector. Biofuels have emerged as a highly promising source of alternative energy, and have drawn global R&D for their production using biomass.